PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA WAROENG MIE LAVA BONDOWOSO - Qibtiyah, Siti Mariyatul; Azhad, Muhamad Naely; Rahayu, Jekti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Based on the phenomenon that occurred in "Waroeng Mie Lava Bondowoso" the researcher found that the ups and downs of consumers when making purchases became a problem in "Waroeng Mie Lava Bondowoso" resulting in consumer satisfaction which was expected to stabilize sales. This study aims to determine product quality, price and location, on consumer satisfaction at Waroeng Mie Lava. This type of research uses quantitative descriptive. The population in this study are consumers who make purchases of Mie Lava at Waroeng Mie Lava Bondowoso. The sample used was 80 respondents with purposive sampling technique. The analysis tool uses multiple linear regression. The results of the study prove that the results of the t-test of product quality are 5.668 and a significant level of 0.000, then Ho is rejected and H1 is accepted. Price variable with t count of 4.237 and a significant level of 0.000, then Ho is rejected and H1 is accepted. Location variable with t count of 2.420 and a significant level of 0.018, then Ho is rejected and H1 is accepted.